Vertical distribution and transformation of phosphorus and iron in paddy soils during the whole growth stage of rice - Li, Yun; Chen, Minghong; Liu, Xuanye (Frontiers in earth science (Lausanne), 2022)
Paddy fields have alternating wet and dry hydrological cycles at different growth stages of rice, driving changes in soil environment and phosphorus (P) transformation and transport. In-situ measurements of dissolved oxygen (DO), iron (Fe), and P concentrations were conducted to determine the vertical distribution of these concentrations together with the hydrological and meteorological data during the whole growth stage. The results demonstrate that soil vertical DO concentrations at different growth stages were greatly influenced by the water level and temperature of the paddy field at the soil-water interface. A strong negative correlation between soil DO and DGT-labile Fe has been observed, whereas a strong positive correlation has been observed between soil Fe concentration and vertical P. In the paddy field, soil DO concentrations were lower during tillering, booting, and heading to flowering than during the other stages. Thus, soluble P fluxes from soil water interfaces (SWIs) to overlying waters were most significant during these three stages. Furthermore, soils in these three stages are capable of sustained release of P and are highly able to buffer P. Consequently, water management in paddy fields should take into account the hydrological environment during these three stages in order to minimize soil P release. The results of our study provide a valuable reference point for controlling soil P and Fe during rice growth.